Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7759/cureus.2384
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Malignant Neoplasms in an Elderly Patient

Abstract: Only a few case reports to date have described patients with three or more cancers. However, the incidence of multiple primary malignancies is increasing due to the improved survival of cancer patients, the prolonged lifespan of the general population, and better diagnostic techniques. This report describes a 73-year-old woman with primary breast, rectal squamous cell, and renal cell carcinomas. This case is unique because, in addition to having three primary malignancies, this patient had rectal squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…There are no currently available standard guidelines for MPMN treatment. Malignancy type, disease stage and the overall health of the patient are each considered (12), and each patient has multidisciplinary individualized treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no currently available standard guidelines for MPMN treatment. Malignancy type, disease stage and the overall health of the patient are each considered (12), and each patient has multidisciplinary individualized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, long-term application of targeted drug therapy may also increase the incidence of secondary malignant tumors. In 2002, Surveillance Epidemiology and End Results data indicated that ~16% of all new cancer cases were secondary or higher-order primary cancer in the United States (12).…”
Section: Discussionmentioning
confidence: 99%
“…Eight cases experienced dead/metastasis or recurrence. [ 3 , 4 , 13 , 16 , 17 , 19 , 20 , 24 ] The outcomes of cases were not reported. [ 6 9 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer and urological tumors. Bladder and breast cancers share extrinsic risk factors (including personal lifestyle, ultraviolet radiation, smoking and alcohol) and some genetic mutations in signal transduction pathways (95,96). Damrauer et al showed that basal-like and luminal-like subtypes of bladder cancer surprisingly reflect the hallmarks of breast biology (97).…”
Section: Breast Cancer and Gynecological Tumorsmentioning
confidence: 99%
“…If the generic association of breast cancer with urological tumors can be considered sporadic (11,12,16,31,44,61,76,86,95,96), the same cannot be said for bladder cancer (11,12,76,95).…”
Section: Breast Cancer and Gynecological Tumorsmentioning
confidence: 99%